Measuring Digitalization of Talent Acquisition Practices And identifying Critical Positions with Employee Branding and Mediating the Role of Technology Resources Strategy - Shayrine H.; Gomathi S. (International Journal of Intelligent Systems and Applications in Engineering, 2022)
This article examined the issues surrounding talent acquisition and how employer branding might assist in resolving some of them. In a competitive environment, organizations struggle to retain skilled and youthful employees. As a result, firms must implement training and development opportunities to retain personnel. With the continuous change of technology in human resources especially in talent acquisition, this study argues that it should not necessarily change HR orientation towards its approach to recruiting practices. The purpose of this research is to look at the impact of talent management (TM) and identify critical positions with employee branding, as well as the role of resource strategy as a mediator. Human Resources departments will have to evaluate and develop innovative methods of working to develop individualized programs for recognizing and engaging people in a continuous learning process. This strategy should become the core of the organization's future culture. The study aims to investigate the topics of employer branding and talent acquisition, as well as the company's tactics, and the data were analyzed using smartPLS-3 software and the PLS-SEM model. Findings reveal that the employees seem to be satisfied with the Talent Acquisition Procedure. A five-component scale with a some-object measurement model has been verified inside the study. This study presents an empirical model to help readers better comprehend the link. The paper identifies recent critical issues in talent management.